1971
DOI: 10.1149/1.2408268
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Behavior of Yttria

Abstract: The electrolytic behavior of Y2Oa was investigated. Within the temperature range 700~176there is no electrolytic domain (tion --0.99), however, a small ionic domain (tion ~ 0.5) does exist and is defined within the following boundaries 11,030 log Pe = --15.84 T(~ --35,300 log Pe ---F 15.59 T(~ and Yttrium sesquioxide, Y203, is the only known solid oxide of yttrium. At room temperature and under one atmosphere pressure it possesses the cubic rare earth type C structure (Ia3) (1,2) with 16 sesquioxide formula un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…15). This is related to the high electrical resistance of the Y 2 O 3 layer [58][59][60][61][62] found in the scale (Figs. 5c, 7c).…”
Section: Microstructure and Chemical Composition Of Oxidation Productmentioning
confidence: 99%
See 3 more Smart Citations
“…15). This is related to the high electrical resistance of the Y 2 O 3 layer [58][59][60][61][62] found in the scale (Figs. 5c, 7c).…”
Section: Microstructure and Chemical Composition Of Oxidation Productmentioning
confidence: 99%
“…Numerous works dedicated to the research of point defect structure and electrical conductivity of pure and doped mono-and polycrystalline yttrium oxide have reported that regardless of the type of dopant and its concentration, Y 2 O 3 is p-type semiconductor at high temperatures and for high oxygen partial pressures. [60][61][62] The conductivity of this oxide is predominantly determined by the ionic component. [60][61][62] Due to the large discrepancies in the values of conductivity and activation energy it is difficult to clearly determine which of the Y 2 O 3 sublattices controls the ionic conductivity of this compound.…”
Section: Microstructure and Chemical Composition Of Oxidation Productmentioning
confidence: 99%
See 2 more Smart Citations